Identification of Candidate Genes for Green Rind Color in Watermelon - Wei Zhou; Licong Yi; Yunqiang Wang; Hongsheng Wang; Qingke Li; Na Wu; Zhaoyi Dai (Plants)
The color of the rind is one of the most crucial agronomic characteristics of watermelon (Citrullus lanatus L.). Its genetic analysis was conducted to provide the identification of genes regulating rind color and improving the quality of watermelon appearance. In this study, a mapping population of 505 F2 plants, derived from a cross between green (CG058) and light-green (CG265) rinds, along with a high-density genetic linkage (average 0.9 cM distance between bin markers), was used to map and identify possible candidate genes. The green rind trait was determined to be regulated by a single Mendelian locus and was precisely located within a 110 kb genomic site on chromosome nine (Chr 9). In the respective region, two potential genes, Cla97C09G175170 and Cla97C09G175180, were substantially downregulated in the light-green rind in comparison to the green rind. Previous studies revealed that Cla97C09G175170, encoding a two-component response regulator-like protein (APRR2), is possibly involved in the green rind trait in watermelon. Virus-induced gene silencing (VIGS) assay confirmed that ClAPRR2 is a key gene responsible for green rind color. Moreover, qRT-PCR analysis revealed that the transcription levels of multiple key genes in the chlorophyll (Chl) biosynthesis pathway were downregulated in the light-green rind relative to the green rind. The current findings have the potential to clarify the regulatory mechanisms that underlie the color of the watermelon rind. These data would provide valuable insights for the targeted molecular design and development of watermelon rinds.